CONSTRUCTIVISM: THE ROOTS OF MILITARY PEDAGOGY? - Juhary, Jowati Binti (PEOPLE: International Journal of Social Sciences, 2017)
This concept paper originates from a bigger documentation, and it attempts to examine the importance of constructivism in building intellectual leaders of characters in Malaysia. It analyses the history and evolution of constructivism. Various theories of learning have been considered but constructivism is imperative as it provides strong theoretical as well as pedagogical links to various methods to teaching and learning. Due to the nature of this paper, it adopts content analysis as its methodological approach. It is found that constructivism offers learning and training principles that suit a military learning environment, referred to by scholars in European countries as military pedagogy. This is because all criteria that are critical for building ‘the guardians’ of a nation, who must be intellectual leaders of characters, such as meaningful classroom engagement, higher order thinking skills, and collaboration, derive from constructivism.